Semiconductor nanostructures : quantum states and electronic transport - Ihn, Thomas (Oxford University Press, 2010)
This introduction to the physics of semiconductor nanostructures and their transport properties emphasizes five fundamental transport phenomena: quantized conductance, tunnelling transport, the Aharonov-Bohm effect, the quantum Hall effect and the Coulomb blockade effect.
Keywords: Semiconductors.; Nanostructures.; Transport theory.; elektronické knihy; electronic books